(untitled) (Agroindustrial Science, 2024)
Poultry farming worldwide presents great development; however, one of the great limitations is the determination of the sex of the embryo in ovo, because on farms birds are raised for two purposes, egg production or meat production, so there is a sex preference. In the commercial egg production line, females are preferred, and newborn males are discarded, millions of chicks being sacrificed worldwide, generating great economic losses; it also represents a serious ethical and animal welfare problem, which is why countries like France and Germany have decreed new regulations that regulate and prohibit the slaughter of male chicks. Multiple optical and non-optical techniques have been proposed for in ovo sexing, but they have not yet been developed at an industrial and commercial level. Of all the available techniques, hyperspectral HSI imaging is shown to be a viable non-invasive and non-destructive technique for in ovo sexing, because it provides extensive spectral information about an egg. In this context, the advances, and approaches of HSI with respect to its potential use in in ovo sexing are discussed. HSIs have demonstrated considerable precision in sexing, however, they present limitations such as complexity in data processing and embryonic development time.